Speaking good Arabic: learners’ perceptions - Che Haron, Sueraya (International Institute for Science, Technology & Education (IISTE), 2012)
Learners’ beliefs and perceptions play an important role in language learning. This paper describes a study investigating the perceptions of good as well as poor Malay speakers of Arabic regarding the Arabic language, and their views on the necessary skills and competencies to become good speakers of Arabic. It highlights the similarities and differences between both Malay groups of Arabic speakers, and explains how their perceptions influence their strategies and performance in learning Arabic speaking skills. The author provides some suggestions for teachers in the concluding section.